2-(2c+3)=-3(3c-4)

Simple and best practice solution for 2-(2c+3)=-3(3c-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-(2c+3)=-3(3c-4) equation:


Simplifying
2 + -1(2c + 3) = -3(3c + -4)

Reorder the terms:
2 + -1(3 + 2c) = -3(3c + -4)
2 + (3 * -1 + 2c * -1) = -3(3c + -4)
2 + (-3 + -2c) = -3(3c + -4)

Combine like terms: 2 + -3 = -1
-1 + -2c = -3(3c + -4)

Reorder the terms:
-1 + -2c = -3(-4 + 3c)
-1 + -2c = (-4 * -3 + 3c * -3)
-1 + -2c = (12 + -9c)

Solving
-1 + -2c = 12 + -9c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '9c' to each side of the equation.
-1 + -2c + 9c = 12 + -9c + 9c

Combine like terms: -2c + 9c = 7c
-1 + 7c = 12 + -9c + 9c

Combine like terms: -9c + 9c = 0
-1 + 7c = 12 + 0
-1 + 7c = 12

Add '1' to each side of the equation.
-1 + 1 + 7c = 12 + 1

Combine like terms: -1 + 1 = 0
0 + 7c = 12 + 1
7c = 12 + 1

Combine like terms: 12 + 1 = 13
7c = 13

Divide each side by '7'.
c = 1.857142857

Simplifying
c = 1.857142857

See similar equations:

| 2/3b9 | | (3x+5)(9x-5)=0 | | 2x^2+3x-2x-3=18 | | 11.5(4+X)= | | 5z+5=6-4z+17 | | 6=a+9 | | sec*x-secx-2=0 | | 2(2y+1)=(5y-2) | | 5x+9+4x=9+8+(-7) | | log(9x^3)=2 | | 7a^2-5a-5=-5 | | X^2-25=10 | | 2(25-5)=2(26+5) | | 5x+9+4x=9+8 | | 21/3×5-11 | | 2/7=x/7 | | (X^-3y^3)^-4/(y^3x^-5)^-5 | | 8x^(13/3)-24=0 | | 2*cosx=2*cos*2x | | 12z-4x=-7 | | 10h-10=10-10h | | x^9/2 | | 38x+66=180 | | 3x-(5x)= | | 2n-4=5n+5 | | 80x^2-720=0 | | 8=3x+bx | | 12z+4x=-7 | | 27q-9=180 | | 112x^2-56x=0 | | 2y-7=5-y | | x+.7y=238 |

Equations solver categories